Stimuli-Responsive Polymeric Nanoplatforms for Cancer Therapy - Chang, Di; Ma, Yuanyuan; Xu, Xiaoxuan; Xie, Jinbing; Ju, Shenghong (Frontiers in Bioengineering and Biotechnology, 2021)
Polymeric nanoparticles have been widely used as carriers of drugs and bioimaging agents due to their excellent biocompatibility, biodegradability, and structural versatility. The principal application of polymeric nanoparticles in medicine is for cancer therapy, with increased tumor accumulation, precision delivery of anticancer drugs to target sites, higher solubility of pharmaceutical properties and lower systemic toxicity. Recently, the stimuli-responsive polymeric nanoplatforms attracted more and more attention because they can change their physicochemical properties responding to the stimuli conditions, such as low pH, enzyme, redox agents, hypoxia, light, temperature, magnetic field, ultrasound, and so on. Moreover, the unique properties of stimuli-responsive polymeric nanocarriers in target tissues may significantly improve the bioactivity of delivered agents for cancer treatment. This review introduces stimuli-responsive polymeric nanoparticles and their applications in tumor theranostics with the loading of chemical drugs, nucleic drugs and imaging molecules. In addition, we discuss the strategy for designing multifunctional polymeric nanocarriers and provide the perspective for the clinical applications of these stimuli-responsive polymeric nanoplatforms.